Target Subsystem of a Management System and Its Assessment - Устенко, А. О.; Малинка, О. Я. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
Target subsystem of enterprise management system is considered, which includes mission and system of goals, needed to support the mission. Goals of an enterprise can be researched at three levels: the local level (goals of a separate structural unit of the socio-economic system), the system (corporate) level – the goals of the social-economic system, and overall system level (in external competitive environment, the main idea is the adaptation of the socio-economic system). A factorparametric approach to the representation of the target subsystem is offered, its basic idea is as follows: integrated system is a set of components, the interaction of which generates new (integrative, system) qualities that are not common for its formation. This system can be very relatively described as a certain set of "factors", reasons, driving forces of its existence and life, each of which is characterized with a certain system of "parameters", and can be measured concerning permanent features and properties of a "factor" (meaning common notions which describe the essence of the components, their properties and features that are used in the description of factors and their parameters in a specific production process). Using the example of a particular company, it is illustrated how to analyze target subsystem of management system.